Exercise and Omega-3 Polyunsaturated Fatty Acid Supplementation for the Treatment of Hepatic Steatosis in Hyperphagic OLETF Rats. (12th September 2011) - Borengasser, Sarah J.; Rector, R. Scott; Uptergrove, Grace M.; Morris, E. Matthew; Perfield, James W.; Booth, Frank W.; Fritsche, Kevin L.; Ibdah, Jamal A.; Thyfault, John P.
Abstract : Background and Aims. This study examined if exercise and omega-3 fatty acid (n3PUFA) supplementation is an effective treatment for hepatic steatosis in obese, hyperphagic Otsuka Long-Evans Tokushima Fatty (OLETF) rats. Methods. Male OLETF rats were divided into 4 groups (n = 8 /group): (1) remained sedentary (SED), (2) access to running wheels; (EX) (3) a diet supplemented with 3% of energy from fish oil (n3PUFA-SED); and (4) n3PUFA supplementation plus EX (n3PUFA+EX). The 8 week treatments began at 13 weeks, when hepatic steatosis is present in OLETF-SED rats. Results. EX alone lowered hepatic triglyceride (TAG) while, in contrast, n3PUFAs failed to lower hepatic TAG and blunted the ability of EX to decrease hepatic TAG levels in n3PUFAs+EX. Insulin sensitivity was improved in EX animals, to a lesser extent in n3PUFA+EX rats, and did not differ between n3PUFA-SED and SED rats. Only the EX group displayed higher complete hepatic fatty acid oxidation (FAO) to CO2 and carnitine palmitoyl transferase-1 activity. EX also lowered hepatic fatty acid synthase protein while both EX and n3PUFA+EX decreased stearoyl CoA desaturase-1 protein. Conclusions. Exercise lowers hepatic steatosis through increased complete hepatic FAO, insulin sensitivity, and reduced expression of de novo fatty acid synthesis proteins while n3PUFAs had no effect.